Alignment Optimization of Elastically Supported Submarine Propulsion Shafting Based on Dynamic Bearing Load Influence Numbers - Jinlin Liu; Zheng Gu; Junhui He; Shijie Cao (Applied Sciences)
The design scheme of elastically supported submarine propulsion shafting can effectively realize the attenuation of the vibration energy and improve the stealth performance of the whole submarine. However, the elastic deformation generated by the system will affect the alignment state of shafting, thus affecting its safety and reliability. Aiming at this problem, taking a certain elastically supported submarine propulsion shafting as the study object of this paper, the alignment calculation model of the shafting was established and validated, and an equivalent line-surface method was proposed to measure the elastic bearing displacement. On this basis, the concept of the dynamic bearing load influence numbers (BLINs) was elicited, and a response surface method using Gaussian process regression (GPR) was designed to establish the mapping relationship between the elastic displacement and the dynamic BLINs. Taking the equivalent displacements of the bearings as variables, the alignment optimization of the shafting was achieved by combining the genetic algorithm and the response surfaces. After optimization, the load of the rear stern bearing was reduced by 16.67%, and the standard deviation of the bearing loads was reduced by 37.19%. Hence, the alignment state of the shafting was improved. The studied results can provide theoretical and technical support for the analysis and optimization of the alignment characteristics of elastically supported submarine propulsion shafting.